Governance of Digital Curriculum in the Public Education Sector - Kadir, Evi Kurnia; Arismunandar, Arismunandar (Program Pascasarjana Universitas Negeri Makassar, 2025)
Digital transformation has brought fundamental changes in education management, especially in the realm of curriculum management. This research aims to analyze the conceptual development and direction of global research regarding digital-based curriculum management and identify the main dimensions that support its implementation in the digital era. The approach used is bibliometric analysis, with data obtained from the Scopus database for the period 2015–2025. A total of 946 documents were analyzed using VOSviewer software to map keyword linkages (co-occurrence analysis) and identify thematic clusters of research. The results of the study show that the topic of digital-based curriculum management is growing rapidly in a multidisciplinary manner, involving the fields of education, computer science, and management. The bibliometric mapping yielded six main clusters that reflect the direction of global research, namely: (1) digital transformation and learning analytics, (2) information systems and educational technology, (3) curriculum management and pedagogical innovation, (4) project and knowledge management, (5) digital repositories and online libraries, and (6) sustainability of higher education. The keywords